SEROPREVALENCE OF ROTA VIRUS IN BOVINES IN AND AROUND JABALPUR DISTRICT OF MADHYA PRADESH - Stheevan, V; Swamy, Madhu; Verma, Yamini; Upadhaya, Ankur Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to detect seroprevalence of bovine Rota virus in diarrheic and non-diarrhoeic bovine calves and adult animals. A total of 82.22 per cent serum samples were found positive for rota virus antibodies with more positive cases in diarrheic animals. The ELISA test was performed on serum sample of 30 buffalo calves and 40 cow calves including both diarrheic and non diarrheic clinical category. The findings revealed 76.66% and 77.5% positive serum samples of buffalo calves and cow calves, respectively for rota virus antibody. In both the group of animals, more number of positive samples were recorded in diarrheic animals.
Keywords: Bovine rotavirus (BRV); ELISA; Diarrhoea; Seroprevalence; Bovine